Injury incidence, severity, and burden in elite youth soccer players – A 3-year prospective study. Issue 9 (September 2022) - Ruf, Ludwig; Altmann, Stefan; Graf, Ferdinand; Romeike, Christian; Wirths, Christian; Wohak, Oliver; Härtel, Sascha
Abstract: Objectives: This study aimed to investigate age-related injury incidence, severity, and burden over a 3-year period in U14 to U19 elite male soccer players in a German youth academy. Design: Descriptive epidemiology study. Methods: Time-loss injuries of 166 unique players were prospectively documented and injury incidence, severity, and burden were calculated for each age group, body part, and type of injuries. Results: A total of 562 time-loss injuries were recorded. Across all age groups (U14 to U19), injury incidence was 42.2 per squad season (ranging from 30.5 in the U19 to 67.7 in the U15), severity was 11.0 days lost (ranging from 8.0 in the U15 to 17.0 in the U17), and burden was 464.1 days lost per squad season (ranging from 304.9 in the U19 to 756.7 in the U14). The thigh, knee and ankle were the body parts with the highest injury incidence (9.2; 5.9; 5.9), severity (11.0; 16.0; 13.0), and burden (101.6; 94.9; 76.1). Cruciate ligament injuries had both the highest burden (164.4) and severity (137.0), and muscle injuries the highest incidence (11.0) of all types of injuries. U15 had the highest injury incidence (67.7) of all age groups. U14 and U17 had both the highest injury severity (15.0; 17.0) and burden (756.7; 618.8) of all age groups. Age-related patterns were observed for selected types of injuries such as muscle injuries, tendinopathy, bone-stress injury, and fractures. Conclusions: Injury incidence, severity, and burden substantially differed descriptively between age groups and clear age-related patterns for selected types of injuries were evident.